Planning practices of Nurse Managers in Ghana - Adelaide Maria Ansah Ofei; Paarima, Yennuten; Theresa Barnes; Atswei Adzo Kwashie (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
Background: Nurse Managers (NMs) has 24-hour duty and responsible in the provision of quality and effective healthcare. Therefore, they are expected to identify trends or challenges, and formulate and implement innovations to assist their ward/unit accomplish the organizational goals. This means NMs are required to understand and effectively use planning as a critical tool for their responsibility. The study explored the planning practices of NMs at the unit level. Methods: A quantitative exploratory design was used to examine the planning practices of NMs in the Greater Accra Region of Ghana. Data was gathered from 522 nurses in 19 healthcare facilities. Data analysis were performed using descriptive and multiple regression analysis. Results: The finding show all the NMs plan at the unit. 59.8% of the NMs have quarterly plans. NMs spend between 60-79% of their time in planning at the unit. Socio-demographic characteristics of NM together explained 2.6% of planning practices. However, only experience as NM significantly contributed to the regression model. Conclusion: Planning practices of NMs in this current study were relatively good and critical analysis of the results indicate that experience as NM was the only predictor of planning practice. This buttress the claim that experience as NM plays a pivotal role in ability to effectively plan at the unit.